Food Intakes and Determinants of Under-5 Health Outcomes in South Africa - Molelekoa, Thonaeng Charity; Oyekale, Abayomi Samuel (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Inadequate food intake has been implicated as the major cause of poor nutritional and health outcomes among children under the age of 5. However, little empirical evidence exists on the role of different food classes in promoting good health outcomes among under-5 children. Therefore, this study analysed the effect of food intakes on the occurrence of wasting, stunting and underweight among under-5 children in South Africa. Subjects and Method: The data were the Demographic and Health Survey (DHS) collected in 2016 with two stage stratified sampling. The z-scores for wasting, stunting and underweight were the indicators of child’s health outcomes, which were analysed with logistic regression model. Results: The logistic regression results revealed that the probability of stunting decreased with being discharged same time with the mother (0.90), residing in wealthy homes (0.90), and being a boy (0.82), but increased with sharing toilet (0.43), and number of children (0.90). In addition, wasting reduced with milk consumption (0.23), high birth weight (1.00) and number of children (1.50). In comparison with Western Cape, a child has 4.92, 7.29, 11.65 and 8.33 higher chances of being underweight when they reside in Kwazulu-Natal, North West, Gauteng and Limpopo province, respectively, while consumption of fruit and vegetables increased underweight. Conclusion: It can be concluded that there is still a nutritional problem on children under 5 in South Africa. It is recommended that government, especially the health department should advise mothers with child health related matters at clinics and encourage them to breastfeed their children and have recommended diet for them.Keywords: health outcomes, underweight, stunting, wasting, child. Correspondence:Thonaeng Charity Molelekoa, Department of Agricultural Economics and Extension, North-West University Mafikeng Campus, Mmabatho 2735 South Africa. Email: Thona.Maselwa@nwu.ac.za.